Changes in cerebral oxygenation and cerebral blood flow during hemodialysis – A simultaneous near-infrared spectroscopy and positron emission tomography study. Issue 2 (February 2020) - Polinder-Bos, Harmke A; Elting, Jan Willem J; Aries, Marcel JH; García, David Vállez; Willemsen, Antoon TM; van Laar, Peter J; Kuipers, Johanna; Krijnen, Wim P; Slart, Riemer HJA; Luurtsema, Gert; Westerhuis, Ralf; Gansevoort, Ron T; et al.
Near-infrared spectroscopy (NIRS) is used to monitor cerebral tissue oxygenation (rSO2 ) depending on cerebral blood flow (CBF), cerebral blood volume and blood oxygen content. We explored whether NIRS might be a more easy applicable proxy to [ 15 O]H2 O positron emission tomography (PET) for detecting CBF changes during hemodialysis. Furthermore, we compared potential determinants of rSO2 and CBF. In 12 patients aged ≥ 65 years, NIRS and PET were performed simultaneously: before (T1), early after start (T2), and at the end of hemodialysis (T3). Between T1 and T3, the relative change in frontal rSO2 (ΔrSO2 ) was −8 ± 9% ( P  = 0.001) and −5 ± 11% ( P  = 0.08), whereas the relative change in frontal gray matter CBF (ΔCBF) was −11 ± 18% ( P  = 0.009) and −12 ± 16% ( P  = 0.007) for the left and right hemisphere, respectively. ΔrSO2 and ΔCBF were weakly correlated for the left (ρ 0.31, P  = 0.4), and moderately correlated for the right (ρ 0.69, P  = 0.03) hemisphere. The Bland-Altman plot suggested underestimation of ΔCBF by NIRS. Divergent associations of pH, pCO2 and arterial oxygen content with rSO2 were found compared to corresponding associations with CBF. In conclusion, NIRS could be a proxy to PET to detect intradialytic CBF changes, although NIRS and PET capture different physiological parameters of the brain.